Bolivia Sixth Review Under the Stand-By Arrangement and Requests for Modification and Waiver of Nonobservance and Applicability of Performance Criteria, Rephasing, and Reduction of Access: Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Bolivia (IMF Staff Country Reports, 2005)
The staff report for the Sixth Review under the Stand-By Arrangement and Requests for Waiver of Performance Criteria on Bolivia highlights economic developments and preliminary macroeconomic framework. The economy is characterized by a number of vulnerabilities that require policy vigilance. These include a highly dollarized financial system subject to deposit runs and a fiscal position sensitive to revenue/expenditure-sharing arrangements between the central and subnational governments. Policies to ensure continued macroeconomic stability will provide continuity and a framework for sound policy action by the successor government